Clinical outcomes and quality of life of patients with short-term and long-term opioid therapy for the treatment of non- cancer pain - Abdullah Sani, Asween Rowena; Zin, Che Suraya (2019)
Introduction: Data from the US showed that there are increasing evidences of opioid-related harms such as opioid overdose deaths in long term opioid use for the treatment of chronic non-cancer pain. There is lack of data from Malaysia on opioid use particularly on its opioid related clinical outcomes.